2018
DOI: 10.4025/actascitechnol.v40i1.35000
|View full text |Cite
|
Sign up to set email alerts
|

<b>Release optimization of fermentable sugars from defatted rice bran for bioethanol production

Abstract: ABSTRACT. The aim of this study was to optimize the enzymatic hydrolysis of defatted rice bran (DRB) for release fermentable sugars with subsequent bioethanol production. Optimization of enzymatic hydrolysis was achieved using a sequential experimental design, performing a fractional factorial design of amyloglucosidase (AMG), at action times of two and three hours, respectively. In bioethanol production, it was evaluated the effect of adding of 15 μL g -1 of protease prior to the action of amylases. Fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…The DRB hydrolysed presented 61.23 ± 0.03 g L -1 of reducing sugars and the wine obtained yielded 3.62 ± 0.23% (v/v) of ethanol. These values was lower than that described by (Siepmann et al, 2018), which optimized the DRB hydrolysis process and obtained 68.8 g L -1 of reducing sugar and 4.0% (v/v) of ethanol. The different values of reducing sugar could be associated with the variations in the raw material composition and it may affect the final ethanol content.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…The DRB hydrolysed presented 61.23 ± 0.03 g L -1 of reducing sugars and the wine obtained yielded 3.62 ± 0.23% (v/v) of ethanol. These values was lower than that described by (Siepmann et al, 2018), which optimized the DRB hydrolysis process and obtained 68.8 g L -1 of reducing sugar and 4.0% (v/v) of ethanol. The different values of reducing sugar could be associated with the variations in the raw material composition and it may affect the final ethanol content.…”
Section: Resultscontrasting
confidence: 66%
“…Enzymatic Hydrolysis: DRB was ground (≅ 70 mesh) in a knife mill (SL 31, Solab, Piracicaba, Brazil) and hydrolysed as previously described by Siepmann et al (2018) in order to release fermentable sugars. The following enzymatic hydrolysis was conducted in a DRB suspension (200 g L -1 ): protease (15 µL g -1 DRB) kept at 60 ºC for 2 h; α-amylase (30 µL g -1 DRB) kept at 90-95 °C for 2 h; and amyloglucosidase (40 µL g -1 DRB) kept at 55-60 °C for 3 h. After hydrolysed, the DRB suspension was centrifuged for 5 min at 3823 g (Rotina 420R, Hettich, Spenge, Germany) and the supernatant were used for vinegar elaboration.…”
Section: Vinegar Productionmentioning
confidence: 99%
“…For all the fermentation media, the ethanol concentration starts to drop from 12 hours of fermentation on. This fact can be justified either via the ethanol consumption by the yeast itself when the substrate concentration was low (Silva et al, 2011), or the ethanol evaporation, phenomenon also observed by Siepmann et al(2018) after 12 hours of fermentation.…”
Section: Batch Fermentationmentioning
confidence: 99%
“…A final ethanol concentration of 35.5 g/L (productivity of 1.5 g/L/h) was achieved by S. cerevisiae grown on enzymatically treated DRB [29]. The conditions of starch enzymatic hydrolysis were optimized in terms of DRB concentration as well as α-amylase and amyloglucosidase concentrations ( Table 2).…”
Section: Production Of Bioethanolmentioning
confidence: 99%